World War I and the triumph of a new Japan, 1919-1930 - Dickinson, Frederick R. (Studies in the social and cultural history of modern warfare, 2013)
A fascinating new, integrative history of interwar Japan that highlights the wide-ranging impact of the Great War far from the Western Front. Adopting a global context, this book reveals how Japan participated wholeheartedly in new post-war projects of democracy, internationalism, disarmament and peace, shaping Japan's twentieth-century world.